Impact of COVID-19 on people with asthma: a mixed methods analysis from a UK wide survey. Issue 1 (13th January 2022) - Philip, Keir Elmslie James; Buttery, Sara; Williams, Parris; Vijayakumar, Bavithra; Tonkin, James; Cumella, Andrew; Renwick, Lottie; Ogden, Lizzie; Quint, Jennifer K; Johnston, Sebastian L; Polkey, Michael I; Hopkinson, Nicholas S
Abstract : Introduction: The impact of acute COVID-19 on people with asthma appears complex, being moderated by multiple interacting disease-specific, demographic and environmental factors. Research regarding longer-term effects in this group is limited. We aimed to assess impacts of COVID-19 and predictors of persistent symptoms, in people with asthma. Methods: Using data from an online UK-wide survey of 4500 people with asthma (median age 50–59 years, 81% female), conducted in October 2020, we undertook a mixed methods analysis of the characteristics and experience of those reporting having had COVID-19. Results: The COVID-19 group (n=471, 10.5%) reported increased inhaler use and worse asthma management, compared with those not reporting COVID-19, but did not differ by gender, ethnicity or household income. Among the COVID-19 group, 56.1% reported having long COVID, 20.2% were 'unsure'. Those with long COVID were more likely than those without long COVID to describe: their breathing as worse or much worse after their initial illness (73.7% vs 34.8%, p<0.001), increased inhaler use (67.8% vs 34.8%, p<0.001) and worse or much worse asthma management (59.6% vs 25.6%, p<0.001). Having long COVID was not associated with age, gender, ethnicity, UK nation or household income. Analysis of free text survey responses identified three key themes: (1) variable COVID-19 severity, duration and recovery; (2) symptom overlap and interaction between COVID-19 and asthma; (3) barriers to accessing healthcare. Conclusions: Persisting symptoms are common in people with asthma following COVID-19. Measures are needed to ensure appropriate healthcare access including clinical evaluation and investigation, to distinguish between COVID-19 symptoms and asthma.